Die Jesus van die geskiedenis: J P Meier se Jesus-proiel krities bekyk - Geyser, P. A. (HTS teologiese studies, 2001)
The Jesus of history: A citical relection on J P Meier's Jesus-proile. This aricle is a critical relecion on the histoical Jesus research of J P Meier. Of the intendedfour volumes two of Meier,s books on Jesus have been published: A marginal Jew: Rethinking the historical Jesus, Vol 1: The roots of the problem and the person (1991); and Vol 2: Mentor, message, and miracles (1994/ A previous article focused on assessing Meier's work in light of the hermeneutical premises prevalent in histoical Jesus studies. In this aricle his proile of the historical Jesus is criically evaluated. Attenion is given to Meier's understanding of Jesus, family and his early career, his birth and descent, his language and education, Jesus as arisan, his unmarried status, the world in which he lived, the last meal, his ministry, his relationship with John the Bapist, his proclamation of the Kingdom of God and his miracles.